Beneficial effects of monounsaturated fatty acid‐rich blended oils with an appropriate polyunsaturated/saturated fatty acid ratio and a low n‐6/n‐3 fatty acid ratio on the health of rats. (9th July 2022) - Yang, Ligang; Yang, Chao; Chu, Chu; Wan, Min; Xu, Dengfeng; Pan, Da; Xia, Hui; Wang, Shao Kang; Shu, Guofang; Chen, Shiqing; Sun, Guiju
Abstract: BACKGROUND: The effects of dietary fat on health are influenced by its fatty acid profile. We aimed to determine the effects of monounsaturated fatty acid (MUFA)‐rich blended oils (BO) containing a balance of polyunsaturated fatty acids (PUFAs) and saturated fatty acids (SFAs) and with a low n‐6/n‐3 PUFA ratio on the health of rats fed normal or high‐fat diets. The BO was obtained by mixing red palm oil, rice bran oil (RO), tea seed oil and flaxseed oil in appropriate proportions. RESULTS: BO consumption reduced the serum low‐density lipoprotein cholesterol (LDL‐C), non‐esterified fatty acid (NEFA), insulin (INS), tumor necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), interleukin‐1 (IL‐1), high‐sensitivity C‐reactive protein (hs‐CRP), malondialdehyde (MDA), lipid peroxide (LPO) and oxidized LDL (ox‐LDL) concentrations and the homeostasis model assessment of insulin resistance (HOMA‐IR); it increased the high‐density lipoprotein cholesterol (HDL‐C), glutathione peroxidase (GSH‐Px) and superoxide dismutase (SOD) concentrations, and the bone mineral density (BMD) versus control oil‐containing normal and high‐fat diets. BO also reduced the triglyceride (TG), hs‐CRP, MDA, ox‐LDL and reactive oxygen species (ROS) concentrations; and increased the serum HDL‐C and SOD, and BMD versus RO‐containing high‐fat diets. Finally, BO reduced the glucose (GLU) and INS, and HOMA‐IR; it increased HDL‐C, SOD, femoral weight and BMD versus RO‐containing normal diets. CONCLUSION: BOs with an appropriate fatty acid profile have beneficial effects on the glucolipid metabolism, inflammation, oxidative stress and bone quality of rats when included in both normal and high‐fat diets. © 2022 Society of Chemical Industry.